Ecological and theological aspects of some animal laws in the Pentateuch - Rao, Chilkuri Vasantha (ISPCK, 2005)
This book investigates the Old Testament rules of behavior and intercourse with animal life and welfare. The author deals with view of the biblical authors on the close relation of God the creator to all living creatures and his care for animals as well as human beings.